IMPACT OF CUTTING CONDITIONS ON THE LOAD ON SERVO MOTORS AT A CNC LATHE IN THE PROCESS OF TURNING A CLUTCH HUB (Balkan Journal of Applied Mathematics and Informatics, 2023)
The purpose of the research in this paper is to investigate the impact of cutting conditions on the load on servo motors at a three-axis computer numerically controlled (CNC) Hitachi Seiki Seicos lathe. The analysed parameters (cutting speed, feed, and depth of cut) play a crucial role in the turning process. It is significant that each cutting condition directly alters the value of the load on the power system and has a significant effect on cutting forces, which in turn affect the load on the servo motors at the CNC lathe during the process.